Peran Inovasi Operasional Berbasis Digital dalam Meningkatkan Daya Saing UMKM - Cynthia Ananda Br Tarigan; Hendestri Br Sembiring; Rissa Yulinda; Siti Marfu’ah Bako; Arsyadona Arsyadona (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to explore the role of digital-based operational innovation in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The background lies in the growing need for MSMEs to adapt to technological advancements in order to maintain their existence and improve business performance amid increasingly intense competition. Using a qualitative approach with a literature review method, data were collected from various credible academic sources published within the last five years (2019–2024), including journals, institutional reports, and relevant literature. The findings reveal that the adoption of technologies such as digital point-of-sale (POS) systems, cloud-based inventory management, and Customer Relationship Management (CRM) significantly contributes to operational efficiency, market expansion, and service quality improvement. However, the digitalization process among MSMEs still faces several challenges, including low digital literacy, limited infrastructure, and inadequate access to training. In conclusion, the success of MSME digital transformation heavily depends on the collaboration between business actors, government, academia, and other stakeholders to build an inclusive and sustainable digital ecosystem.